2013
DOI: 10.1016/j.jalz.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Infantile exposure to lead and late‐age cognitive decline: Relevance to AD

Abstract: Background Early-life lead (Pb) exposure induces overexpression of the amyloid beta precursor protein and its amyloid beta product in older rats and primates. We exposed rodents to Pb during different life span periods and examined cognitive function in old age and its impact on biomarkers associated with Alzheimer’s disease (AD). Methods Morris, Y, and the elevated plus mazes were used. Western blot, quantitative polymerase chain reaction (qPCR), and enzyme-linked immunosorbent assay were used to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 26 publications
9
72
1
Order By: Relevance
“…While there are no conclusive evidence available which can pin point a precise correlation between Pb exposure and AD, however studies in the ageing individuals have shown a possible association between Pb exposure and cognitive decline in human subjects (Nordberg et al, 2000, Weisskopf et al, 2007). This was corroborated by recent findings from a 2-year lifespan study in rodents which demonstrated that rodents with developmental exposure to Pb showed cognitive deficit as aged adults, which is consistent with changes in amyloid biomarkers of AD (Bihaqi et al, 2013). …”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…While there are no conclusive evidence available which can pin point a precise correlation between Pb exposure and AD, however studies in the ageing individuals have shown a possible association between Pb exposure and cognitive decline in human subjects (Nordberg et al, 2000, Weisskopf et al, 2007). This was corroborated by recent findings from a 2-year lifespan study in rodents which demonstrated that rodents with developmental exposure to Pb showed cognitive deficit as aged adults, which is consistent with changes in amyloid biomarkers of AD (Bihaqi et al, 2013). …”
Section: Introductionsupporting
confidence: 82%
“…Studies have also revealed that cognitive deficit caused by childhood Pb exposure can prevail in adulthood (Mazumdar et al, 2011). Although Pb exposure has been projected as a risk factor for the health of adults and young ones, studies carried out in our lab on rodents and primates have provided strong proof indicating that early life exposure is associated with latent effects contributing to the neurodegenerative process (Bihaqi et al, 2011, Bihaqi et al, 2013). …”
Section: Discussionmentioning
confidence: 90%
“…Similar observations were made in old rats (18-20 months) after early life exposure to Pb (0.2% in drinking water from postnatal day 1 to 20) Bihaqi et al, 2014). This was associated with cognitive impairment that was observed only if animals were exposed when young (Bihaqi et al, 2014). Adult exposure may also increase the risk of neurodegeneration, as suggested by the two following studies: -human Tg-SwD1 APP transgenic mice treated with Pb (27 mg/kg/day by gavage) for 6 weeks beginning at 8 weeks of age showed increased accumulation of Abeta and amyloid plaques (Gu et al, 2012).…”
supporting
confidence: 82%
“…Similarly, monkeys exposed during infancy to Pb (1 mg/kg/day from birth to 400 days) showed in aging (23 y old) an overexpression of APP and Abeta (Bihaqi et al, 2011), and of Tau mRNA and protein (Bihaqi and Zawa, 2013). Similar observations were made in old rats (18-20 months) after early life exposure to Pb (0.2% in drinking water from postnatal day 1 to 20) Bihaqi et al, 2014). This was associated with cognitive impairment that was observed only if animals were exposed when young (Bihaqi et al, 2014).…”
supporting
confidence: 79%
“…In addition to its well-characterized developmental neurotoxicity, cumulative lead exposure can also cause neurological impairment in adults (van Wijngaarden et al, 2009). Monkeys and rats exposed to low concentrations of lead have increased cognitive decline and Alzheimer’s disease-associated neuropathology later in life (Basha et al, 2005; Wu et al, 2008; Bihaqi et al, 2013; Grossman, 2014). Furthermore, longitudinal studies from a cohort of non-occupationally exposed elderly men found an association between relatively low blood (mean 5.5 μg/dL) and/or patella lead levels and increased cognitive decline (Payton et al, 1998; Weisskopf et al, 2004).…”
Section: Introductionmentioning
confidence: 99%